2008
DOI: 10.1002/ijc.23425
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of CYP3A5 polymorphisms along the androgen metabolism pathway in prostate cancer

Abstract: Prostate cancer is a leading solid tumor among men in the Western world. Androgens play an important role in the carcinogenesis and treatment of prostate cancer. CYP3A5 is a cytochrome P450 superfamily member which also has activity in testosterone metabolism. In this study, we looked for two-gene interactions associated with clinical characteristics of prostate cancer in the Finnish population. We used multifactor-dimensionality reduction for the identification of the two-gene interactions in androgen metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Highly similar frequencies were observed for German, Finnish, Swedish and Greek populations [2,7,11,14,17,22]. Interestingly, the allelic frequencies described in our work are not significantly different from the ones published for the Baltic Sea area.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Highly similar frequencies were observed for German, Finnish, Swedish and Greek populations [2,7,11,14,17,22]. Interestingly, the allelic frequencies described in our work are not significantly different from the ones published for the Baltic Sea area.…”
Section: Resultssupporting
confidence: 84%
“…These CYP3A5 genotypes have been associated with the lower mean clearances of benzodiazepines and etopo- USA/(Afro-Americans) Healthy adults, (34) 0.721 0.279 [9] Finnish/(Caucasians) Healthy adults, (754) 0.070 0.930 [22] USA/(Afro-Americans) Healthy adults, (25) 0.540 0.460 [11] side, which might increase the probability of drugrelated adverse reactions, such as peripheral neuropathy [16]. Additionally, a strong association between the CYP3A5*1 genotype and tacrolimus dose requirement was observed.…”
Section: Resultsmentioning
confidence: 99%
“…6 We demonstrated that the rs776746 A allele was associated with developing PCa in South African white men, whereas in Finnish men the allele was not associated with development of PCa but was associated with bone metastases (disease progression). 5 The (10) 17 (6) 1.83 (0.92 -3.74) 0.0869 0.1312* *Corrected p-value for the effect of population stratification in coloured men obtained by multiplying age-adjusted value by an inflation factor λ = 3.06 (Fernandez et al, 2008 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…4 In Finnish men, the rs776746 A allele was significantly associated with PCa bone metastases. 5 The CYP3A4 enzyme is involved in the oxidation of testosterone to 2β-, 6β-or 15β-hydroxytestosterone. For the SNP rs2740574 (-392A>G; the A allele = CYP3A4*1A and G allele = CYP3A4*1B) in the 5´ regulatory region of the gene, the G allele was initially shown to be associated with PCa in white and black American men, 6 which was replicated in subsequent investigations.…”
Section: Original Articlesmentioning
confidence: 99%
“…For this reason, CYP3A5*1 is considered a protective genotype of prostate cancer, and an association between CYP3A5*3 and prostate cancer risk has been demonstrated. 42 Therefore, a second possibility is that a portion of endogenous estradiol derived from testosterone might be modulated by the CYP3A5*1 genotype to result in a lower breast cancer risk among CYP3A5*1 carriers in JB and NJB. Further studies are required to confirm whether the CYP3A5*3 mutation is associated with an increased or decreased risk of breast cancer.…”
Section: Discussionmentioning
confidence: 99%